Integrated Analysis of Long Noncoding RNA Expression Profiles in Acute-on-Chronic Liver Failure. (19th May 2021) - Fu, Xiaoyu; Cheng, Da; Ouyang, Yi; Li, Ying; Li, Ronghua; Peng, Shifang; Fu, Lei
Abstract : People infected with chronic hepatitis B virus (HBV) might progress to acute-on-chronic liver failure (ACLF) with a high fatality rate. Long noncoding RNAs (lncRNAs) are involved in human diseases, but it is unknown whether lncRNAs are involved in the progression of chronic HBV infection to ACLF. Hence, this study is aimed at systemically identifying and characterizing the landscape and the molecular mechanism of lncRNAs in the pathogenesis of chronic HBV infection progress to ACLF. RNA sequencing (RNA-Seq) of peripheral blood samples from 5 ACLF and 5 HBV infection patients was performed. We detected 9733 lncRNAs, including 406 annotated lncRNAs and 9327 novel lncRNAs. A total of 407 lncRNAs were found to be significantly dysregulated in the patients with ACLF as compared with those in the chronic HBV infection patients. The flanking protein-coding genes of differentially expressed lncRNAs were enriched with pathways that might contribute to the pathogenesis of ACLF, such as the WNT signaling pathway. Furthermore, 9 selected differentially expressed lncRNAs validated by the qRT-PCR, showing that the expression patterns of these 9 lncRNAs were consistent with the RNA-Seq data. Four selected differentially expressed lncRNAs were also validated in another patient cohort comprising 80 patients with ACLF and 65 patients with chronic HBV infection. Aberrant lncRNAs might be used to develop novel diagnostic biomarkers or drug targets for ACLF.